REDESIGN LOGO WINNIE FRUIT PADANG - Alfi Fikri Fermana, Dr. M. Nasrul Kamal, M.Sn., (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
Winnie Fruit is one of the cafes that sells a variety of processed fruits into fresh and healthy preparations with the target audience of people who like a healthy lifestyle by consuming processed fruit. Winnie Fruit soup shop has similarities with other competitors and the use of media that supports Winnie Fruit soup shop logo is not yet effective.The design of this logo redesign considers layout and typography in order to achieve the purpose of the logo in an identity. Logo with shape, color, style of design that will form a new perception in the minds of the target community and increase the Winnie Fruit market so that it has a good image and has its own characteristics that are easily remembered by the target audience.The analytical method used is the SWOT analysis, Strength, Weakness, Oppurtunity, and Threat. to find solutions to problems encountered. The design process starts from data collection, observation and interviews with Winnie Fruit soup shop owner to find some weaknesses in Winnie Fruit products and collect the data needed to redesign. Supporting media used to support the main media in the form of manual books include stationery sets, packaging, menus, dress codes, aprons, sign table numbers, posters, shopping bags, x-banners, stickers.Keywords: redesign, logo, cafe, fruits